ANALYSIS OF TALENT POOL MANAGEMENT (TALENT MANAGEMENT) IN IMPROVING ORGANIZATIONAL PERFORMANCE OF PT PLN MAIN UNIT DISTRIBUTION OF NORTH SUMATRA UP3 RANTAUPRAPAT - Cosine Melvin Sitorus Pane; Nazaruddin; Iskandarini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Employee performance can optimize the quality and quantity of production with more productive performance. Making employees or employees more able to explore the knowledge and skills needed to achieve company or organizational goals. The effect of talent pool management on organizational performance is a complex research topic, but in general it can be said that good management talent pool has the potential to improve overall organizational performance. Human resource management is carried out using a process of analyzing, developing and utilizing talent in a sustainable and effective way to meet business needs, in other words this is talent management. Talent management according to Wibowo (2020) is a concept that starts from how to plan, acquire, develop,